Solution growth of chalcopyrite compounds single crystal. (July 2015) - Nagaoka, Akira; Nose, Yoshitaro; Miyake, Hideto; Scarpulla, Michael A.; Yoshino, Kenji
Abstract: I–III–VI2 chalcopyrite compound Cu(In x, Ga1− x )Se2 (CIGS) single crystal were successfully grown by traveling heater method (THM). The powder X-ray diffraction (XRD) pattern of the CIGS showed preferred orientations of (112), (220) and (312) planes, confirming the chalcopyrite structure. In Raman spectra, the A1 mode peaks expected for CIGS were observed, and no secondary phases were observed. The full-width at half-maximum (FWHM) of the X-ray rocking curve (XRC) for the (112) oriented CIGS single crystal is 103 arcsec. The composition of the CIGS single crystal was homogeneous and the stoichiometric ratio of CIGS was found to be slightly Cu-poor, In-rich, Ga-rich and Se-poor. The good-quality single-phase CIGS single crystals can be obtained from these results. Highlights: Main purpose is preparation of large-size CIGS (In/Ga = 8/2) single crystal growth by THM, which is one of the solution growth. A CIGS single crystal was grown from 80 mol% In solution at 850 °C. We investigated the structural, compositional and electrical properties for CIGS single crystal.